INTERNATIONAL YOUTH MEETING IN FORMATION OF INTERCULTURAL COMPETENCE OF FUTURE SPECIALISTS - Halytska, Maya M. (Educological discourse, 2014)
This article analyzes the concept of "intercultural learning", "intercultural education", "intercultural competence and expertise." The problem of formation of intercultural competence of the individual, is the guarantor of effective dialogue of cultures in the world. Emphasized the important role of international youth meetings in the formation of intercultural competence of professionals. It is shown that the cost of values including intercultural competences in the overall education system is to establish close contacts between individuals and subjects of international events.